Devonian formations, vertebrate faunas and age control on the far south coast of New South Wales and adjacent Victoria - Young, G. C. (Australian journal of earth sciences, 2007)
A diverse fossil vertebrate record in the Devonian of coastal southeastern Australia includes at least 30 genera and species representing all three major groups of extant jawed vertebrates (bony and cartilaginous fishes, and tetrapods), and both extinct groups (placoderm and acanthodian fishes). A bone recorded by W. B. Clarke in 1860 from Twofold Bay is the first published record of a Devonian vertebrate from the Southern Hemisphere. Abundant plant remains at some localities include large impressions of arborescent lycopsids, indicating one of the earliest forest environments for the Gondwana supercontinent. An early terrestrial invertebrate fauna is evidenced by fossil millipede remains. A review of the evidence for age control using paleontology and isotopic dating suggests that the lower part of the Devonian sequence (Bunga beds, Boyd Volcanic Complex) may be somewhat older (Emsian - Eifelian) than recently proposed; the tetrapod trackways at Genoa River in Victoria (lower part of the Combyingbar Formation) may correlate with the lowermost Twofold Bay Formation of the Merrimbula Group, which is overlain by the marine Bellbird Creek Formation, a manifestation of the global late Frasnian marine transgression and extinction event. Abundant placoderm remains at all higher fossil fish horizons in the overlying Worange Point Formation indicate a latest Devonian rather than Carboniferous age for the upper Merrimbula Group.